Bismuth vanadate / titanium dioxide heterojunction photo-anode and preparation method thereof

The synthesis of bismuth vanadate/titanium dioxide heterojunction through one hydrothermal reaction on the bismuth vanadate photoelectrode has been solved, and the charge separation efficiency of bismuth vanadate photoelectrode has been significantly improved, thus achieving high-efficiency photoelectrochemical decomposition and other applications with low cost and simple steps.

CN119786271APending Publication Date: 2025-04-08XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510008159.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing bismuth vanadate photoelectrodes have low photoelectrochemical performance due to the high recombination rate of photogenerated electron-hole pairs, making it difficult to effectively improve their charge separation efficiency.

Method used

By using Ti3C2Tx aqueous solution as the titanium source, a simple hydrothermal reaction was used to synthesize bismuth vanadate/titanium dioxide heterojunction photoanode, which significantly improved its charge separation efficiency and photoelectrochemical performance.

Benefits of technology

This method has low cost and simple steps, which significantly improves the charge separation efficiency and photoelectrochemical performance of BiVO4 photoanode, and has important scientific significance and application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005227563110000011
    Figure HDA0005227563110000011
  • Figure HDA0005227563110000012
    Figure HDA0005227563110000012
  • Figure HDA0005227563110000021
    Figure HDA0005227563110000021
Patent Text Reader

Abstract

The invention discloses a bismuth vanadate / titanium dioxide heterojunction photo-anode and a preparation method thereof. The preparation method comprises the following steps: preparing nanosheet-shaped titanium carbide through hydrofluoric acid etching and ultrasonic separation, then preparing a titanium carbide aqueous solution with a certain concentration, transferring the prepared titanium carbide aqueous solution into a hydrothermal kettle with a polytetrafluoroethylene liner, putting a bismuth vanadate photo-anode into the hydrothermal kettle, and after hydrothermal reaction is completed, obtaining the bismuth vanadate / titanium dioxide heterojunction photo-anode. The prepared bismuth vanadate / titanium dioxide heterojunction photoanode has good charge separation efficiency and photoelectrochemical performance, and can be used in the fields of photoelectrochemical water decomposition, photoelectrochemical sensors, photoelectrochemical degradation of organic pollutants and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nano-functional electrode materials and green energy technology, and specifically relates to a bismuth vanadate / titanium dioxide heterojunction photoanode and a preparation method thereof. The prepared bismuth vanadate / titanium dioxide heterojunction photoanode has good charge separation efficiency and photoelectrochemical performance, and can be used in photoelectrochemical water decomposition, photoelectrochemical sensors, photoelectrochemical degradation of organic pollutants and other fields. Background Art

[0002] With the increasing depletion of fossil fuel combustion and the resulting air and water pollution, the search for alternative clean energy has attracted extensive research from researchers around the world. Photoelectrochemical water splitting to produce hydrogen is an emerging technology that uses semiconductor photoelectrodes to produce hydrogen without carbon emissions. It can effectively respond to the country's call for "carbon peak and carbon neutrality"; and the most critical part of this technology is the development of cheap, efficient and stable semiconductor photoelectrodes.

[0003] Bismuth vanadate (BiVO4) has a suitable band gap (2.4 eV) and a large theoretical photocurrent density (7.5 mA cm -2 ) and good visible light absorption ability, and is considered to be one of the most promising photoelectrode materials; however, the high recombination rate of photogenerated electron-hole pairs is one of the main reasons affecting its photoelectrochemical performance, and constructing a heterojunction is one of the most effective strategies to improve its photogenerated carrier separation efficiency.

[0004] BiVO4 / TiO2 heterojunctions have been widely used in photoelectrocatalytic water decomposition, photocatalytic water decomposition, and degradation of organic pollutants. For example: Emre et al. (ACS Appl. Mater. Interfaces 2021, 13, 60602-60611) significantly improved the water oxidation activity of BiVO4 photoanode by a TiO2 capping layer prepared by atomic layer deposition, which was attributed to the enhancement of charge separation and the suppression of surface recombination by surface state passivation. Hu et al. (Applied Surface Science 2018, 436, 319-326) synthesized BiVO4 / TiO2 by sol-gel method and simple hydrothermal method, and found that BiVO4 / TiO2 is an excellent photocatalyst for degrading benzene. However, current reports are limited to the use of multi-step and complex methods to construct heterojunctions between bismuth vanadate and titanium dioxide.

[0005] Therefore, we designed a novel method to utilize Ti3C2T x The preparation method of BiVO4 / TiO2 heterojunction is synthesized in one step by a simple hydrothermal reaction using aqueous solution as titanium source, which can significantly improve the charge separation efficiency and photoelectrochemical performance of BiVO4 photoanode, and has important scientific significance and application value. Summary of the invention

[0006] The purpose of the present invention is to provide a bismuth vanadate / titanium dioxide heterojunction photoanode and a preparation method thereof, which has the advantages of high efficiency, stable performance and simple method. The bismuth vanadate / titanium dioxide heterojunction can significantly improve the charge separation efficiency and photoelectrochemical performance of the BiVO4 photoanode.

[0007] The technical solution of the present invention is as follows:

[0008] A bismuth vanadate / titanium dioxide heterojunction photoanode and a preparation method thereof, characterized in that nano-sheet titanium carbide is prepared by hydrofluoric acid etching and ultrasonic separation, and then a titanium carbide nanosheet aqueous solution of a certain concentration is prepared, the prepared titanium carbide aqueous solution is transferred to a polytetrafluoroethylene inner hydrothermal reactor, and then the bismuth vanadate photoanode is placed therein. After the hydrothermal reaction is completed, a composite photoanode, i.e., a BiVO4 / TiO2 heterojunction, is obtained. The specific steps are as follows:

[0009] (1) 1 g of aluminum titanium carbide was dissolved in 15 mL of HF solution and stirred for 24 h, centrifuged and washed 6 times until neutral, and then vacuum dried to obtain a black powder, i.e., multilayer titanium carbide;

[0010] (2) dissolving the multilayer titanium carbide in 500 mL of ultrapure water, ultrasonicating for 5 h in an argon atmosphere at 0°C, centrifuging at 8000 rpm for 20 min, taking the supernatant, filtering, and vacuum drying to obtain nanosheet-shaped titanium carbide;

[0011] (3) preparing a certain concentration of titanium carbide nanosheet aqueous solution, stirring it evenly and then ultrasonicating it for 1 hour to make the titanium carbide nanosheets evenly dispersed in the aqueous solution;

[0012] (4) The titanium carbide aqueous solution prepared in step (3) is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, and a BiVO4 electrode is placed in the hydrothermal reactor containing the titanium carbide aqueous solution, reacted at a certain temperature for 30 to 60 minutes, washed and vacuum dried to obtain a BiVO4 / TiO2 heterojunction.

[0013] Furthermore, in step (3), the concentration of the titanium carbide nanosheet aqueous solution is 0.3 to 0.9 mg / mL.

[0014] Furthermore, in step (4), the hydrothermal reaction temperature is 90 to 150°C.

[0015] The beneficial effects of the present invention are:

[0016] The preparation method of the present invention is low in cost and simple in method. The BiVO4 / TiO2 heterojunction prepared by the hydrothermal method can effectively improve the carrier separation efficiency and the photoelectrochemical performance of BiVO4, and has important scientific significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a transmission electron microscope image of the BiVO4 / TiO2 heterojunction; the lattice spacing of 0.327nm belongs to the (110) crystal plane of TiO2, and the lattice spacing of 0.314nm belongs to the (-130) crystal plane of BiVO4, indicating the formation of a BiVO4 / TiO2 heterojunction.

[0018] Figure 2 XPS graph of Ti element in BiVO4 / TiO2 heterojunction; Ti 2p 1 / 2 and Ti 2p 3 / 2 Belong to Ti 4+ , indicating the formation of TiO2.

[0019] Figure 3 Figure 2 is the charge separation efficiency diagram of BiVO4 / TiO2 heterojunction and BiVO4 electrode. Compared with BiVO4 electrode, the charge separation efficiency of BiVO4 / TiO2 heterojunction is significantly improved.

[0020] Figure 4 This is the photoelectrochemical performance test of the optimized BiVO4 / TiO2 heterojunction and BiVO4 electrode, that is, the linear scanning curve under simulated sunlight; it can be seen from the figure that the photoelectrochemical performance of the BiVO4 / TiO2 heterojunction is significantly better than that of the BiVO4 electrode. DETAILED DESCRIPTION

[0021] The technical solution and implementation method of the present invention are described below by way of embodiments, but the technical solution and implementation method of the present invention are not limited to the following embodiments.

[0022] Example 1

[0023] (1) 3.32 g of potassium iodide was dissolved in 50 mL of ultrapure water and stirred until clear, then 0.97 g of bismuth nitrate pentahydrate was added and stirred for 1 h until completely dissolved, and then the pH was adjusted to 1.7 by adding HNO3, which was recorded as solution A; 20 mL of 0.23 mol / L p-benzoquinone ethanol solution was prepared, and the prepared p-benzoquinone ethanol solution was added to solution A and stirred for several minutes to obtain a dark red electrolyte;

[0024] (2) The FTO conductive glass was ultrasonically cleaned with ultrapure water, isopropanol, acetone, ethanol and ultrapure water in sequence, and FTO was used as the working electrode for electrodeposition in the electrolyte prepared in step (1) for 320 seconds, and finally a red BiOI film was deposited on the surface of the FTO, and then vacuum dried;

[0025] (3) dropping 55 μL of 0.08 mol / L acetylacetonato vanadyl dimethyl sulfoxide solution onto the surface of the BiOI film prepared in step (2), calcining at 450° C. for 2 h in a muffle furnace to obtain a BiVO4 photoanode containing impurities, and then successively immersing in a sodium hydroxide solution (1 mol / L) and deionized water to clean the anode, and then naturally drying to obtain a pure BiVO4 photoanode;

[0026] (4) 1 g of aluminum titanium carbide was dissolved in 15 mL of HF solution (40%) and stirred for 24 h, centrifuged and washed 6 times until neutral, and then vacuum dried to obtain a black powder, i.e., multilayer titanium carbide;

[0027] (5) dissolving the multilayer titanium carbide prepared in step (4) in 500 mL of ultrapure water, ultrasonicating for 5 h in an argon atmosphere at 0° C., centrifuging at 8000 rpm for 20 min, taking the supernatant, filtering, and vacuum drying to obtain nanosheet-shaped titanium carbide;

[0028] (6) preparing a 0.3 mg / mL titanium carbide aqueous solution, and transferring it to a hydrothermal reactor with a polytetrafluoroethylene liner after ultrasonication for 1 h;

[0029] (7) The BiVO4 photoanode prepared in step (3) is placed in a reaction kettle containing titanium carbide aqueous solution (with the BiVO4 side facing downward), reacted at 90° C. for 30 min, washed and vacuum dried to obtain a BiVO4 / TiO2 heterojunction.

[0030] Example 2

[0031] (1) 3.32 g of potassium iodide was dissolved in 50 mL of ultrapure water and stirred until clear, then 0.97 g of bismuth nitrate pentahydrate was added and stirred for 1 h until completely dissolved, and then the pH was adjusted to 1.7 by adding HNO3, which was recorded as solution A; 20 mL of 0.23 mol / L p-benzoquinone ethanol solution was prepared, and the prepared p-benzoquinone ethanol solution was added to solution A and stirred for several minutes to obtain a dark red electrolyte;

[0032] (2) The FTO conductive glass was ultrasonically cleaned with ultrapure water, isopropanol, acetone, ethanol and ultrapure water in sequence, and FTO was used as the working electrode for electrodeposition in the electrolyte prepared in step (1) for 320 seconds, and finally a red BiOI film was deposited on the surface of the FTO, and then vacuum dried;

[0033] (3) dropping 55 μL of 0.08 mol / L acetylacetonato vanadyl dimethyl sulfoxide solution onto the surface of the BiOI film prepared in step (2), calcining at 450° C. for 2 h in a muffle furnace to obtain a BiVO4 photoanode containing impurities, and then successively immersing in a sodium hydroxide solution (1 mol / L) and deionized water to clean the anode, and then naturally drying to obtain a pure BiVO4 photoanode;

[0034] (4) 1 g of aluminum titanium carbide was dissolved in 15 mL of HF solution (40%) and stirred for 24 h, centrifuged and washed 6 times until neutral, and then vacuum dried to obtain a black powder, i.e., multilayer titanium carbide;

[0035] (5) dissolving the multilayer titanium carbide prepared in step (4) in 500 mL of ultrapure water, ultrasonicating for 5 h in an argon atmosphere at 0° C., centrifuging at 8000 rpm for 20 min, taking the supernatant, filtering, and vacuum drying to obtain nanosheet-shaped titanium carbide;

[0036] (6) preparing a 0.5 mg / mL titanium carbide aqueous solution, and transferring it to a hydrothermal reactor with a polytetrafluoroethylene liner after ultrasonication for 1 h;

[0037] (7) The BiVO4 photoanode prepared in step (3) is placed in a reaction kettle containing titanium carbide aqueous solution (with the BiVO4 side facing downward), reacted at 105° C. for 30 min, washed and vacuum dried to obtain a BiVO4 / TiO2 heterojunction.

[0038] Example 3

[0039] (1) 3.32 g of potassium iodide was dissolved in 50 mL of ultrapure water and stirred until clear, then 0.97 g of bismuth nitrate pentahydrate was added and stirred for 1 h until completely dissolved, and then the pH was adjusted to 1.7 by adding HNO3, which was recorded as solution A; 20 mL of 0.23 mol / L p-benzoquinone ethanol solution was prepared, and the prepared p-benzoquinone ethanol solution was added to solution A and stirred for several minutes to obtain a dark red electrolyte;

[0040] (2) The FTO conductive glass was ultrasonically cleaned with ultrapure water, isopropanol, acetone, ethanol and ultrapure water in sequence, and FTO was used as the working electrode for electrodeposition in the electrolyte prepared in step (1) for 320 seconds, and finally a red BiOI film was deposited on the surface of the FTO, and then vacuum dried;

[0041] (3) dropping 55 μL of 0.08 mol / L acetylacetonato vanadyl dimethyl sulfoxide solution onto the surface of the BiOI film prepared in step (2), calcining at 450° C. for 2 h in a muffle furnace to obtain a BiVO4 photoanode containing impurities, and then successively immersing in a sodium hydroxide solution (1 mol / L) and deionized water to clean the anode, and then naturally drying to obtain a pure BiVO4 photoanode;

[0042] (4) 1 g of aluminum titanium carbide was dissolved in 15 mL of HF solution (40%) and stirred for 24 h, centrifuged and washed 6 times until neutral, and then vacuum dried to obtain a black powder, i.e., multilayer titanium carbide;

[0043] (5) dissolving the multilayer titanium carbide prepared in step (4) in 500 mL of ultrapure water, ultrasonicating for 5 h in an argon atmosphere at 0° C., centrifuging at 8000 rpm for 20 min, taking the supernatant, filtering, and vacuum drying to obtain nanosheet-shaped titanium carbide;

[0044] (6) preparing a 0.7 mg / mL titanium carbide aqueous solution, and transferring it to a hydrothermal reactor with a polytetrafluoroethylene liner after ultrasonication for 1 h;

[0045] (7) The BiVO4 photoanode prepared in step (3) is placed in a reaction kettle containing titanium carbide aqueous solution (with the BiVO4 side facing downward), reacted at 120°C for 45 minutes, washed and vacuum dried to obtain a BiVO4 / TiO2 heterojunction.

[0046] Example 4

[0047] (1) 3.32 g of potassium iodide was dissolved in 50 mL of ultrapure water and stirred until clear, then 0.97 g of bismuth nitrate pentahydrate was added and stirred for 1 h until completely dissolved, and then the pH was adjusted to 1.7 by adding HNO3, which was recorded as solution A; 20 mL of 0.23 mol / L p-benzoquinone ethanol solution was prepared, and the prepared p-benzoquinone ethanol solution was added to solution A and stirred for several minutes to obtain a dark red electrolyte;

[0048] (2) The FTO conductive glass was ultrasonically cleaned with ultrapure water, isopropanol, acetone, ethanol and ultrapure water in sequence, and FTO was used as the working electrode for electrodeposition in the electrolyte prepared in step (1) for 320 seconds, and finally a red BiOI film was deposited on the surface of the FTO, and then vacuum dried;

[0049] (3) dropping 55 μL of 0.08 mol / L acetylacetonato vanadyl dimethyl sulfoxide solution onto the surface of the BiOI film prepared in step (2), calcining at 450° C. for 2 h in a muffle furnace to obtain a BiVO4 photoanode containing impurities, and then successively immersing in a sodium hydroxide solution (1 mol / L) and deionized water to clean the anode, and then naturally drying to obtain a pure BiVO4 photoanode;

[0050] (4) 1 g of aluminum titanium carbide was dissolved in 15 mL of HF solution (40%) and stirred for 24 h, centrifuged and washed 6 times until neutral, and then vacuum dried to obtain a black powder, i.e., multilayer titanium carbide;

[0051] (5) dissolving the multilayer titanium carbide prepared in step (4) in 500 mL of ultrapure water, ultrasonicating for 5 h in an argon atmosphere at 0° C., centrifuging at 8000 rpm for 20 min, taking the supernatant, filtering, and vacuum drying to obtain nanosheet-shaped titanium carbide;

[0052] (6) preparing a 0.9 mg / mL titanium carbide aqueous solution, and transferring it to a hydrothermal reactor with a polytetrafluoroethylene liner after ultrasonication for 1 h;

[0053] (7) The BiVO4 photoanode prepared in step (3) is placed in a reaction kettle containing titanium carbide aqueous solution (with the BiVO4 side facing downward), reacted at 150° C. for 60 min, washed and vacuum dried to obtain a BiVO4 / TiO2 heterojunction.

[0054] Example 5

[0055] Photoelectrochemical tests of BiVO4 / TiO2 heterojunction and BiVO4 electrode

[0056] The BiVO4 / TiO2 heterojunction and BiVO4 electrode prepared in Example 2 were used as working electrodes, silver / silver chloride electrode was used as reference electrode, and platinum electrode was used as counter electrode to form a three-electrode system, which was connected to an electrochemical workstation. 50mL of 1mol / L KBO3 solution (pH 9.3) was added to a quartz electrolytic cell, and the test method of the linear scanning curve was used to measure that the photocurrent density of the BiVO4 / TiO2 heterojunction was increased by about 1 times compared with the BiVO4 photoanode, and the charge separation efficiency was increased by 47% (bias 1.23V vs.RHE). Therefore, the preparation method of the BiVO4 / TiO2 heterojunction electrode of the present invention has good practical application value.

[0057] The above embodiments are not limitations of the present invention, and the present invention is not limited to the above embodiments. As long as the requirements of the present invention are met, they belong to the protection scope of the present invention.

Claims

1. A bismuth vanadate / titanium dioxide heterojunction photoanode and a preparation method thereof, characterized in that: Nano-sheet titanium carbide is prepared by hydrofluoric acid etching and ultrasonic separation, and then a certain concentration of titanium carbide nanosheet aqueous solution is prepared, and the prepared titanium carbide aqueous solution is transferred to a polytetrafluoroethylene inner hydrothermal reactor, and then the bismuth vanadate photoanode is placed therein. After the hydrothermal reaction is completed, the composite photoanode, i.e., BiVO4 / TiO2 heterojunction, is obtained. The specific steps are as follows: (1) 1 g of aluminum titanium carbide was dissolved in 15 mL of HF solution and stirred for 24 h, centrifuged and washed 6 times until neutral, and then vacuum dried to obtain a black powder, i.e., multilayer titanium carbide; (2) dissolving the multilayer titanium carbide in 500 mL of ultrapure water, ultrasonicating for 5 h in an argon atmosphere at 0°C, centrifuging at 8000 rpm for 20 min, taking the supernatant, filtering, and vacuum drying to obtain nanosheet-shaped titanium carbide; (3) preparing a certain concentration of titanium carbide nanosheet aqueous solution, stirring it evenly and then ultrasonicating it for 1 hour to make the titanium carbide nanosheets evenly dispersed in the aqueous solution; (4) The titanium carbide aqueous solution prepared in step (3) is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, and a BiVO4 electrode is placed in the hydrothermal reactor containing the titanium carbide aqueous solution, reacted at a certain temperature for 30 to 60 minutes, washed and vacuum dried to obtain a BiVO4 / TiO2 heterojunction.

2. The preparation method according to claim 1, characterized in that The concentration of the titanium carbide nanosheet aqueous solution in step (3) is 0.3-0.9 mg / mL.

3. The preparation method according to claim 1, characterized in that: The hydrothermal reaction temperature in step (4) is 90-150°C.